Faktor - Faktor yang Berhubungan dengan Kejadian Perlengketan Plasenta (Retensio Placenta) di Rumah Sakit Islam Jakarta Cempaka Putih: Sebuah Studi Kasus Kontrol - Fenny Apriana Permatasari; Sarah Handayani; Emma Rachmawati (ARKESMAS [Arsip Kesehatan Masyarakat], 2017)
Factors Associated with Retained Placenta (Retensio Placenta) Case in Cempaka Putih Jakarta Islamic Hospital: A Case Control Study Introduction. Retained placenta can cause life-threatening because it relates with bleeding and infection due toretained placenta complication. Various factors such as age, paritas, history of birth complications, pregnanciesinterval, and some other factor can affect the occurrence of retained placenta. This study aimed to determine thefactors associated with the incidence of retained placenta at Rumah Sakit Islam Jakarta Cempaka Putih in 20102016.Methods.This study was a quantitative study with case-control design. It was conducted in Rumah Sakit IslamJakarta Cempaka Putih and data collection conducted in November 2016. Population in case group was all womanwho deliver with retained placenta case and population in control group was all women who deliver withoutretained placenta case during 2010 – 2016. The number of samples in this study are 84 people who qualified theinclusion criteria of this study whereas 42 respondents as a control group and 42 respondents as a case group. Datacollection conducted by viewing secondary data which is medical record. The data from medical record includespatient identity, age, education, parity, distance of pregnancy, anemia status and complication history. The dataanalysis used an univariat and bivariat analysis (Chi-square test).Results. Respondent proportion on the case group mostly aged no-risk (81%), had high education (66,7%), hadparity no-risk (92,9%), had pregnancies interval no-risk (57,1%), had anemia (59,5%) and had no history of birthcomplication (61,9%). There is correlation between the retained placenta with education (p value 0,003) andanemia status (Pvalue 0,049). Conclusions. The result showed there was a correlation between the incidence of retensia placenta with the level ofeducation (p value = 0,003) in addition, there is also a relationship between the incidence of retensia placenta withanemia status (p value = 0,049).